Technical analysis on Singapore stocks - La, Kim Phung (2009)
Though sometimes being criticized and judged against fundamental analysis and other hypothesis such as Efficient Market Hypothesis or Random Walk Theory, in reality, one cannot deny that technical analysis is widely used by many investors everyday.